Digital communications test and measurement high-speed physical layer characterization - Derickson, Dennis; Muller, Marcus (Prentice Hall modern semiconductor design series. Prentice Hall signal integrity library, 2008)
As digital communications systems move to higher and higher speeds, engineers are faced with challenges not just in design, but also in testing and measuring those systems. This is a guide to the testing and measurement of these systems.